Hydrogen-based shaft furnace pellet reduction bonding behavior evaluation method

Through simplified experimental steps and multiple evaluation methods, combined with rotary drum and electronic universal testing machine, the complexity and accuracy of the evaluation of bonding behavior of hydrogen-based vertical furnace pellets is solved, and low-cost and high-accuracy adhesives are achieved Determination of the junction index.

CN119198529AInactive Publication Date: 2024-12-27CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411118102.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing methods for evaluating the bonding behavior of hydrogen-based vertical furnace pellets are complex, costly and inconvenient, which affects the accuracy of the bonding index, especially in the dispersion and breaking of the remaining pellets.

Method used

Using a method including test sample preparation, gas composition and flow determination, heating and cooling, test temperature control, pressure reduction, dispersion operation and result representation, the bonding is calculated by combining the drum and the electronic universal test machine. The degree index and bond strength index simplify the experimental process and improve data accuracy.

Benefits of technology

It achieves low cost and simple operation, and can quickly measure the bond strength index and bond degree index of DRI, improving the sensitivity and accuracy of the measurement results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a hydrogen-based shaft furnace pellet reduction bonding behavior evaluation method, and relates to the technical field of hydrogen-based shaft furnaces. The method comprises the following steps: S1, preparing a test sample, selecting pellet particles to prepare the test sample, putting the test sample into a furnace before the test sample is prepared, drying the test sample at 105 + / -5 DEG C, and then cooling the test sample to room temperature; s2, determining gas composition and flow; s3, heating and cooling gas, wherein the heating and cooling gas is nitrogen; s4, testing the temperature; s5, pressure bearing of the test sample; s6, performing reduction; s7, performing dispersion operation; and S8, representing a result, and determining a bonding degree exponential expression. The invention provides an evaluation index suitable for bonding of hydrogen-based shaft furnace pellets. The index has the advantages that the index is low in cost, simple and easy to obtain; the operation is simple, and the bonding strength index and the bonding degree index of the DRI can be measured in a short time; the caking index measurement result is higher in sensitivity, and the data is more accurate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen-based vertical furnaces, and in particular to a method for evaluating reduction and bonding behavior of hydrogen-based vertical furnace pellets. Background Art

[0002] my country has a large output of crude steel, but faces severe pressure to reduce carbon emissions. In the short term, measures such as blast furnace-converter long process technology and management optimization can achieve low-carbon emission production of steel; in the medium term, the promotion and application of hydrogen-based vertical furnace direct reduction ironmaking process and scrap steel + electric furnace short process can achieve the production of "green steel" and meet user needs; in the long term, new hydrogen-based direct reduction ironmaking technologies such as hydrogen-based vertical furnace and circulating fluidized bed will be the key measures to achieve low-carbon green transformation of the steel industry. With the rapid development of hydrogen production technology, the stable supply of cheap green hydrogen resources and the implementation of carbon reduction subsidies and carbon tax policies, the application of hydrogen-based direct reduction ironmaking technology will accelerate my country's steel industry into a higher-quality low-carbon green development stage.

[0003] Hydrogen-based shaft furnace direct reduction is a low-carbon green ironmaking process that can replace blast furnace ironmaking. That is, by using hydrogen-rich gas (natural gas or coke oven gas) as a reducing agent, iron ore is converted into solid direct reduced iron (DRI), and then it is added to the electric furnace (EAF) with scrap steel as raw materials for further smelting to produce molten steel. This process uses hydrogen instead of carbon as a reducing agent to control carbon emissions from the source, and the carbon reduction can reach more than 50% compared with blast furnace ironmaking. However, during the reduction of pellets, due to the generation of fibrous metallic iron and the formation of low-melting-point substances, the low-melting-point substances will generate liquid phases at local high temperatures and eventually cause the direct reduced iron (DRI) to bond, affecting the reduction degree and metallization rate of DRI. Severe bonding will affect the reduction process, resulting in the DRI reduction degree and metallization rate not meeting the requirements for entering the furnace, and secondly, it is difficult to discharge the material, affecting the smooth running of the shaft furnace charge. Therefore, clarifying the bonding behavior of pellets during hydrogen-based reduction is crucial for the smooth running of hydrogen-based shaft furnaces. In summary, an evaluation index suitable for the sticking of pellets in hydrogen-based vertical furnaces is proposed, which can provide a reference for the evaluation of the sticking behavior of pellets in hydrogen-based vertical furnaces.

[0004] GBT24237-2009 / ISO11256:2007 Method for determination of agglomeration properties of iron ore pellets for direct reduction furnace charge.

[0005] The principle of this method is to use a reducing gas composed of hydrogen, carbon monoxide, carbon dioxide and nitrogen to pressurize and isothermally reduce the test sample on a fixed test bench at a temperature of 850°C to achieve a reduction rate of 95%. Use a specified drum to disperse the agglomerated test sample. After the specified dispersion operation is completed, the agglomeration index is calculated from the still aggregated pellets.

[0006] Each sample is taken at least 5 times, each 2000g1g. The loading device provides a completely constant pressure of 147kPa2kPa. The reducing gas is composed of (H2-CO-CO2--N2) and the gas flow rate is L / min0.5L / min. The nitrogen flow rate is controlled at 40L / min during the heating and cooling stages. The drum equipment is made of 5mm thick steel plate, with an inner diameter of 1000mm and an inner length of 500mm. Two parallel steel angle handles with a cross-sectional size of 50mm50mm5mm and a length of 500mm are firmly welded in the drum at equal distances.

[0007] The earliest method to study the bonding properties of pellets was the HYL method, which is suitable for the study of the bonding properties of pellets in the direct reduction process. The specific research method is as follows: 1.2 kg of pellets are placed in a high-temperature furnace at 1223K for reduction. The reducing atmosphere simulates the reducing atmosphere of the HYL vertical furnace. After 30 minutes of reduction, the pellets are taken out and cooled in a protective atmosphere. Then, the reduced pellet agglomerates are subjected to a drop test from a height of 1m. They are dropped 20 times, and the mass percentage of the remaining agglomerates after each drop is recorded. Finally, the mass percentage of the remaining agglomerates is plotted into a curve. The area under the curve represents the degree of bonding, which is called the bonding index. When the bonding index is 0%, it means that there is no bonding of pellets during the reduction process. When the bonding index is 100%, it means that no pellets are scattered from the agglomerates during the falling process. When the bonding index is lower than 25%, the HYL direct reduction process can proceed smoothly.

[0008] GBT24237-2009 / ISO11256:2007 Method for determining the agglomeration of iron ore pellets for direct reduction furnace charge: The bonding index is determined by a rotary drum. This method requires a large amount of charge in the reduction process (5 groups of samples, 2000g each), a large flow rate of reducing gas (the flow rate of N2 in the heating and cooling stages is 20L / min, and the flow rate of reducing gas in the reduction stage is 40L / min), and the composition of the reducing gas (H2-CO-CO2--N2) is relatively simple, which cannot simulate the complex atmosphere of pellet reduction in a hydrogen-based vertical furnace. The agglomeration index is determined by a rotary drum. The rotary drum equipment is made of a 5mm thick steel plate, with an inner diameter of 1000mm and an inner length of 500mm. The equipment is large in size, and the agglomeration index calculated at the end can only indicate the agglomeration of the pellet bonding, and does not explain the bonding behavior (bonding degree, bonding strength). In summary, the entire agglomeration determination process is more complicated to operate, the cost is high, and it is not easy to obtain, which is not easy to achieve for laboratory operation.

[0009] In the HYL method, it is the problem of defining the critical state of bonding, that is, the problem of calculating the percentage of residual agglomerates. During the test, it was found that after the reduction of the residual agglomerates of the pellets fell, the residual agglomerates of the pellets would be dispersed into several small agglomerates instead of a single agglomerate. Some agglomerates were composed of several agglomerates, some agglomerates were composed of non-integer agglomerates, and the agglomerates were even broken. These phenomena make it difficult to calculate the percentage of residual agglomerates, which directly affects the accuracy of the bonding index.

[0010] Therefore, a new solution to the above problems needs to be proposed. Summary of the invention

[0011] The object of the present invention is to provide a method for evaluating the reduction and bonding behavior of hydrogen-based shaft furnace pellets to solve the problems raised in the background technology.

[0012] To achieve the above object, the present invention provides the following technical solution: a method for evaluating the reduction bonding behavior of hydrogen-based shaft furnace pellets, comprising at least the following steps:

[0013] S1: Prepare the test sample. Select pelletized ore particles to prepare the test sample. Before preparing the sample, the test sample should be placed in a furnace, dried at 105℃±5℃, and then cooled to room temperature;

[0014] S2: Determine gas composition and flow rate;

[0015] S3: Heating and cooling gas, the heating and cooling gas is nitrogen, the impurities contained in it shall not exceed 0.1%. 2 The flow rate is controlled at 6L / min. When the temperature is constant at 900℃, the flow rate is controlled at 6L / min. In the cooling stage N 2 The flow rate is controlled at 6L / min;

[0016] S4: Test temperature. The reducing gas should be preheated before entering the reduction test tube so that the temperature inside the reduction test tube and the test sample is maintained at 900℃±5℃ during the entire reduction stage.

[0017] S5: The test sample is under pressure. After 60 minutes of reduction reaction, a constant pressure of 147 kPa + 2 kPa is applied to the test sample by a wind press.

[0018] S6: Restore;

[0019] S7: Dispersion operation;

[0020] S8: Display the results and determine the adhesion index. The adhesion index determination includes a drum method and an electronic universal testing machine method.

[0021] Further, the pellet size range in S1 is divided into two parts, one of which is 10.0 mm to 12.5 mm, and the other is 12.5 mm to 16.0 mm;

[0022] The pellet screening method adopts the method provided in GB / T10322.1;

[0023] S1 is to prepare 1 test sample, the mass of the test sample is m 0 =500g±0.3g.

[0024] Furthermore, the reducing gas in S2 has the following composition:

[0025] H 2 60%±1.0%; CO25%±1.0%; CO 2 3%±1.0%; H 2 O1%±1.0%; CH 4 5%±1.0%; N 2 6%±1.0%;

[0026] During the test, the flow rate of reducing gas should be maintained at 6L / min±0.1L / min.

[0027] Furthermore, the S6 at least includes the following steps:

[0028] In order to make the gas pass through the test sample evenly, a porous sieve plate is first laid at the bottom of the reduction test tube, and a layer of porcelain balls is laid on the sieve plate. After the test sample is loaded, a layer of porcelain balls is laid on the upper layer, and the surface is made flat. In order to prevent the test sample from sticking to the inner wall of the test tube, some ceramic fibers are laid on the inner wall of the reduction test tube;

[0029] Pass nitrogen through the reduction test tube at a flow rate of 6 L / min and start heating;

[0030] When the temperature of the test sample approaches 900°C, increase the nitrogen flow rate to 6L / min and continue heating at this flow rate. After the temperature reaches 900°C, continue heating for 10 minutes.

[0031] Taking the trivalent iron state as the reference, the calculation expression is as follows:

[0032]

[0033] Where:

[0034] m 0 ——The mass of the sample, in g;

[0035] m 1 ——The mass of the sample before reduction begins, in g;

[0036] m2 ——The mass of the sample after reduction tmin, in g;

[0037] W 1 ——FeO content in the sample before the test, unit: %;

[0038] W 2 ——TFe content in the sample before the test, unit: %;

[0039] In the experimental results, the offline weighing method was used to compare the final reduction degree.

[0040] Further, the S7 at least includes the following steps:

[0041] First, carefully take out the reduced test sample from the reduction tube and weigh its entire mass;

[0042] During the operation, some individual small balls will fall off the sticky mass. Remove these small balls and record the mass of the sticky mass, which is composed of two or more pellets.

[0043] Secondly, the drum method is selected and applied. The sticky mass is placed in the drum and rotated for 35 revolutions in total. The whole process is performed 5 times and 7 times. After each dispersal operation, the remaining balls are weighed and their mass is recorded. Before each dispersal operation, the single balls that fall from the sticky mass should be taken out.

[0044] Finally, an electronic universal testing machine was used to apply constant pressure to the agglomerated DRI, and the percentage of the remaining agglomerated mass after the pressure was applied was calculated. A curve was plotted between the number of applications and the percentage of the agglomerated mass each time, and the area ratio under the curve was defined as the bonding strength index.

[0045] Further, the operation of determining the bonding degree index by the drum method is as follows:

[0046] The bond strength index is calculated using formula (2) and expressed as a percentage:

[0047]

[0048] Where:

[0049] Cl——bonding index;

[0050] m r ——Total mass of the test sample after reduction, in g;

[0051] m c,i ——The mass of the sticky mass after i times of dispersing operations, in g.

[0052] Furthermore, the operation of determining the bonding index by the electronic universal testing machine is as follows:

[0053] The mass percentage of agglomeration obtained after each application of pressure is plotted on the coordinate axis, with the horizontal axis being the number of applications and the vertical axis being the mass percentage of agglomeration after each application of pressure. Connect the points with a curve to draw a trend curve, and find the equation of the curve δ=f(n). The bonding strength index can be calculated according to the following formula (3);

[0054]

[0055] Where: f(n) is the relationship equation between the bonding percentage δn and the number of times of pressure applied n, S 0 is the area of ​​the entire coordinate region;

[0056] Bonding index (η): The calculation method can be expressed by the mass of bonded pellets or the number of bonded pellets.

[0057] The quality of the bonded pellets is as follows:

[0058]

[0059] Where:

[0060] m 0 ——Initial mass of pellets, m 0 =500g;

[0061] m a ——Bonding mass of pellets after reduction, g;

[0062] The quality of the bonded pellets is as follows:

[0063]

[0064] Where:

[0065] R——The initial number of pellets, in pieces;

[0066] R a ——The number of sticky particles in the pellet after reduction, in particles.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] The present invention proposes an evaluation index suitable for hydrogen-based shaft furnace pellet bonding, which has the advantages of low cost, simple and easy to obtain; simple operation, and the bonding strength index and bonding degree index of DRI can be measured in a short time; the bonding index measurement result is more sensitive and the data is more accurate. DETAILED DESCRIPTION

[0069] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.

[0070] A method for evaluating the reduction bonding behavior of hydrogen-based shaft furnace pellets comprises at least the following steps:

[0071] S1: Prepare the test sample. Select pelletized ore particles to prepare the test sample. Before preparing the sample, the test sample should be placed in a furnace, dried at 105℃±5℃, and then cooled to room temperature;

[0072] S2: Determine gas composition and flow rate;

[0073] S3: Heating and cooling gas, the heating and cooling gas is nitrogen, the impurities contained in it shall not exceed 0.1% (volume fraction). 2 The flow rate is controlled at 6L / min. When the temperature is constant at 900℃, the flow rate is controlled at 6L / min. In the cooling stage N 2 The flow rate is controlled at 6L / min;

[0074] S4: Test temperature. The reducing gas should be preheated before entering the reduction test tube so that the temperature inside the reduction test tube and the test sample is maintained at 900℃±5℃ during the entire reduction stage.

[0075] S5: The test sample is under pressure. After 60 minutes of reduction reaction, a constant pressure of 147 kPa + 2 kPa is applied to the test sample by a wind press.

[0076] S6: Restore;

[0077] S7: Dispersion operation;

[0078] S8: Display the results and determine the adhesion index. The adhesion index is determined by a rotary drum method and an electronic universal testing machine method.

[0079] The pellet size range in S1 is divided into two parts, one of which is 10.0mm-12.5mm and the other is 12.5mm-16.0mm;

[0080] The screening method of pellets adopts the method provided in GB / T10322.1;

[0081] S1 is to prepare 1 test sample, the mass of the test sample is m 0 =500g±0.3g.

[0082] The reducing gas in S2 has the following composition:

[0083] H 2 60%±1.0%; CO25%±1.0% (volume fraction); CO2 3%±1.0%; H 2 O1%±1.0%; CH 4 5%±1.0%; N 2 6%±1.0%;

[0084] During the test, the flow rate of reducing gas should be maintained at 6L / min±0.1L / min.

[0085] S6 at least comprises the following steps:

[0086] In order to make the gas pass through the test sample evenly, a porous sieve plate is first laid at the bottom of the reduction test tube, and a layer of porcelain balls is laid on the sieve plate. After the test sample is loaded, a layer of porcelain balls is laid on the upper layer, and the surface is made flat. In order to prevent the test sample from sticking to the inner wall of the test tube, some ceramic fibers are laid on the inner wall of the reduction test tube;

[0087] Pass nitrogen through the reduction test tube at a flow rate of 6 L / min and start heating;

[0088] When the temperature of the test sample approaches 900°C, increase the nitrogen flow rate to 6L / min and continue heating at this flow rate. After the temperature reaches 900°C, continue heating for 10 minutes.

[0089] According to the national standard "Determination of reduction index, final reduction degree and metallization rate of iron ore for direct reduction furnace" (GB / T24236-2009), the reduction degree is based on the trivalent iron state, and the degree of deoxidation achieved after a certain period of reduction is expressed in mass percentage. In this experiment, RI is used to represent the reduction index of sintered ore under non-standard state. Based on the trivalent iron state, the calculation expression (1) is:

[0090]

[0091] Where:

[0092] m 0 ——The mass of the sample, in g;

[0093] m 1 ——The mass of the sample before reduction begins, in g;

[0094] m 2 ——The mass of the sample after reduction tmin, in g;

[0095] W 1 ——FeO content in the sample before the test, unit: %;

[0096] W 2 ——TFe content in the sample before the test, unit: %;

[0097] In the experimental results, the offline weighing method was used to compare the final reduction degree.

[0098] S7 at least includes the following steps:

[0099] First, carefully remove the reduced test sample from the reduction tube and weigh its total mass (m r );

[0100] During the operation, some individual balls will fall off the sticky mass. Remove these balls and record the mass of the sticky mass (m c,1 ), the sticky mass is two or more pellets sticking together;

[0101] This operation is considered the first dispersion operation. Removing the test sample from the reduction tube is a critical step and should be performed carefully to avoid premature dispersion of the test sample.

[0102] Next, the drum method was selected and applied. The sticky balls were placed in the drum (25 r / min) and the drum was rotated for a total of 35 revolutions. The whole process was performed 7 times in 5 circles. After each dispersal operation, the remaining balls were weighed and their mass (m c,2 , m c,3 , m c,4 , ...., m c,8 ), individual small balls that fall from the sticky mass should be removed before each dispersing operation;

[0103] Finally, an electronic universal testing machine was used to apply constant pressure to the agglomerated DRI (the descending rate was 15 mm / min and the fixed-point displacement was 2 mm). The percentage of the remaining agglomerated mass after the pressure was applied was calculated, and a curve was plotted between the number of applications and the percentage of the agglomerated mass each time. The area ratio under the curve was defined as the bonding strength index (SI).

[0104] The operation of determining the adhesion index by drum method is as follows:

[0105] The bond strength index is calculated using formula (2) and expressed as a percentage:

[0106]

[0107] Where:

[0108] Cl——bonding index;

[0109] m r ——Total mass of the test sample after reduction, in g;

[0110] m c,i ——The mass of the sticky mass after i times of dispersing operations, in g.

[0111] The operation of determining the adhesion index by electronic universal testing machine is as follows:

[0112] The mass percentage of agglomeration obtained after each application of pressure is plotted on the coordinate axis, with the horizontal axis being the number of applications and the vertical axis being the mass percentage of agglomeration after each application of pressure. Connect the points with a curve to draw a trend curve, and find the equation of the curve δ=f(n). The bonding strength index can be calculated according to the following formula (3);

[0113]

[0114] Where: f(n) is the relationship equation between the bonding percentage δn and the number of times of pressure applied n, S 0 is the area of ​​the entire coordinate region;

[0115] Bonding index (η): The calculation method can be expressed by the mass of bonded pellets or the number of bonded pellets.

[0116] The quality of the bonded pellets is as follows:

[0117]

[0118] Where:

[0119] m 0 ——Initial mass of pellets, m 0 =500g;

[0120] m a ——Bonding mass of pellets after reduction, g;

[0121] The quality of the bonded pellets is as follows:

[0122]

[0123] Where:

[0124] R——The initial number of pellets, in pieces;

[0125] R a ——The number of sticky particles in the pellet after reduction, in particles.

[0126] Table 1 Adhesion degree range

[0127]

[0128] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for evaluating the reduction and bonding behavior of hydrogen-based shaft furnace pellets, characterized in that: At least the following steps are included: S1: Prepare the test sample. Select pelletized ore particles to prepare the test sample. Before preparing the sample, the test sample should be placed in a furnace, dried at 105℃±5℃, and then cooled to room temperature; S2: Determine gas composition and flow rate; S3: Heating and cooling gas, the heating and cooling gas is nitrogen, the impurities contained in it shall not exceed 0.1%, the N2 flow rate is controlled at 6L / min during the heating stage, when the temperature is constant at 900℃, the flow rate is controlled at 6L / min, and the N2 flow rate is controlled at 6L / min during the cooling stage; S4: Test temperature. The reducing gas should be preheated before entering the reduction test tube so that the temperature inside the reduction test tube and the test sample is maintained at 900℃±5℃ during the entire reduction stage. S5: The test sample is under pressure. After 60 minutes of reduction reaction, a constant pressure of 147 kPa + 2 kPa is applied to the test sample by a wind press. S6: Restore; S7: Dispersion operation; S8: Display the results and determine the adhesion index. The adhesion index determination includes a drum method and an electronic universal testing machine method.

2. The method for evaluating reduction bonding behavior of hydrogen-based shaft furnace pellets according to claim 1, characterized in that: The pellet size range in S1 is divided into two parts, one of which is 10.0mm-12.5mm and the other is 12.5mm-16.0mm; The screening method of the pellets adopts the method provided in GB / T10322.1; The S1 is for preparing one test sample, and the mass of the test sample is m0=500g±0.3g.

3. The method for evaluating reduction bonding behavior of hydrogen-based shaft furnace pellets according to claim 1, characterized in that: The reducing gas in S2 has the following composition: H260%±1.0%; CO25%±1.0%; CO23%±1.0%; H2O1%±1.0%; CH45%±1.0%; N26%±1.0%; During the test, the flow rate of reducing gas should be maintained at 6L / min±0.1L / min.

4. The method for evaluating reduction bonding behavior of hydrogen-based shaft furnace pellets according to claim 1, characterized in that: The S6 at least comprises the following steps: In order to make the gas pass through the test sample evenly, a porous sieve plate is first laid at the bottom of the reduction test tube, and a layer of porcelain balls is laid on the sieve plate. After the test sample is loaded, a layer of porcelain balls is laid on the upper layer, and the surface is made flat. In order to prevent the test sample from sticking to the inner wall of the test tube, some ceramic fibers are laid on the inner wall of the reduction test tube; Pass nitrogen through the reduction test tube at a flow rate of 6 L / min and start heating; When the temperature of the test sample approaches 900°C, increase the nitrogen flow rate to 6L / min and continue heating at this flow rate. After the temperature reaches 900°C, continue heating for 10 minutes. Taking the trivalent iron state as the reference, the calculation expression is as follows: Where: m0——mass of the sample, unit: g; m1——the mass of the sample before reduction begins, in g; m2——the mass of the sample after reduction tmin, in g; W1——FeO content in the sample before the test, unit: %; W2——TFe content in the sample before the test, unit: %; In the experimental results, the offline weighing method was used to compare the final reduction degree.

5. The method for evaluating reduction bonding behavior of hydrogen-based shaft furnace pellets according to claim 1, characterized in that: The S7 at least comprises the following steps: First, carefully take out the reduced test sample from the reduction tube and weigh its entire mass; During the operation, some individual small balls will fall off the sticky mass. Remove these small balls and record the mass of the sticky mass, which is composed of two or more pellets. Secondly, the drum method is selected and applied. The sticky mass is placed in the drum and rotated for 35 revolutions in total. The whole process is performed 5 times and 7 times. After each dispersal operation, the remaining balls are weighed and their mass is recorded. Before each dispersal operation, the single balls that fall from the sticky mass should be taken out. Finally, an electronic universal testing machine was used to apply constant pressure to the agglomerated DRI, and the percentage of the remaining agglomerated mass after the pressure was applied was calculated. A curve was plotted between the number of applications and the percentage of the agglomerated mass each time, and the area ratio under the curve was defined as the bonding strength index.

6. The method for evaluating reduction and bonding behavior of hydrogen-based shaft furnace pellets according to claim 1, characterized in that: The operation of determining the adhesion index by the drum method is as follows: The bond strength index is calculated using formula (2) and expressed as a percentage: Where: Cl——bonding index; m r ——Total mass of the test sample after reduction, in g; m c,i ——The mass of the sticky mass after i times of dispersing operations, in g.

7. The method for evaluating reduction bonding behavior of hydrogen-based shaft furnace pellets according to claim 1, characterized in that: The operation of determining the bonding index by the electronic universal testing machine is as follows: The mass percentage of agglomeration obtained after each application of pressure is plotted on the coordinate axis, with the horizontal axis being the number of applications and the vertical axis being the mass percentage of agglomeration after each application of pressure. Connect the points with a curve to draw a trend curve, and find the equation of the curve δ=f(n). The bonding strength index can be calculated according to the following formula (3); Where: f(n) is the relationship equation between the bonding percentage δn and the number of pressure applied n, S0 is the area of ​​the entire coordinate region; Bonding index (η): The calculation method can be expressed by the mass of bonded pellets or the number of bonded pellets. The quality of the bonded pellets is as follows: Where: m0——initial mass of pellets, m0=500g; m a ——Bonding mass of pellets after reduction, g; The quality of the bonded pellets is as follows: Where: R——The initial number of pellets, in pieces; R a ——The number of sticky particles in the pellet after reduction, in particles.

Citation Information

Patent Citations

  • Method for improving drum strength of chromium-containing vanadium-titanium sinter

    CN104388669A

  • Method for determining characteristic number of bonding strength of sintered ores

    CN107101898A

  • Method for detecting reduction bonding strength of pellets

    CN117782803A

  • Preparation of feed material for a blast furnace

    US3946098A